Laminate, piezoelectric device using same, method for manufacturing laminate, and method for manufacturing piezoelectric device

The laminate structure with orientation control layers addresses the challenge of achieving high crystal orientation in thin piezoelectric films, improving energy conversion efficiency for high-frequency devices by adjusting crystal growth consistency and confining vibrational energy.

JP7615439B2Active Publication Date: 2025-01-17NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020156573
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-24
Filing Date
2020-09-17
Publication Date
2025-01-17
Estimated Expiration
2040-09-17

AI Technical Summary

Technical Problem

Existing piezoelectric devices face challenges in achieving high crystal orientation for thin films required for high-frequency applications, particularly in the sub-6 GHz band, due to insufficient lattice matching and initial crystal disorder, which affects energy conversion efficiency.

Method used

A laminate structure is introduced with a first wurtzite thin film, a first hexagonal metal layer, a first electrode layer, a second hexagonal metal layer, and a second wurtzite thin film, where orientation control layers adjust crystal growth consistency, enabling good crystal orientation even in submicron thicknesses.

Benefits of technology

The laminate structure achieves high crystal orientation in thin piezoelectric layers, enhancing energy conversion efficiency and vibrational energy confinement, suitable for high-frequency devices like BAW filters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615439000001
    Figure 0007615439000001
  • Figure 0007615439000002
    Figure 0007615439000002
  • Figure 0007615439000003
    Figure 0007615439000003
Patent Text Reader

Abstract

To provide a laminate having sufficient crystal orientation, even in a region in which a piezoelectric layer is of submicron thickness, and a piezoelectric device using the same.SOLUTION: A laminate includes a first wurtzite thin film, a first hexagonal metal layer, a first electrode layer, a second hexagonal metal layer, and a second wurtzite thin film which are laminated in the order, the first electrode layer being formed from a metal material having a higher acoustic impedance than the second wurtzite thin film.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate, a piezoelectric device using the same, and a method for manufacturing the same, and in particular to a thin film laminate for high frequency use and a piezoelectric device. [Background technology]

[0002] Conventionally, piezoelectric elements that utilize the piezoelectric effect of materials have been used. The piezoelectric effect is a phenomenon in which a material is polarized in proportion to the pressure when pressure is applied to it. Various sensors are made using the piezoelectric effect, such as pressure sensors, acceleration sensors, and AE (acoustic emission) sensors that detect elastic waves.

[0003] In recent years, bulk acoustic wave (BAW) filters have been used as high-frequency bandpass noise filters for smartphones, and wurtzite-type piezoelectric thin films are used in BAW filters. BAW filters operate on the vibration of the piezoelectric thin film in the thickness direction (thickness vibration), so they require a piezoelectric film with high crystal orientation, with the crystal orientation facing in the same direction.

[0004] BAW filters improve their performance by trapping the generated vibration energy within a piezoelectric thin film, so the electrodes must be made of a heavy metal that has high density, Young's modulus, and high acoustic impedance.

[0005] However, in general, lamination of a metal having a high acoustic impedance and a wurtzite thin film has a low degree of lattice matching, which causes the crystal orientation of the wurtzite piezoelectric thin film to become disordered.

[0006] To solve this problem, a structure has been proposed in which a first wurtzite type piezoelectric thin film, a functional material layer serving as an electrode, and a second wurtzite type piezoelectric thin film are formed in this order on a substrate. This laminated structure improves the lattice matching between the functional material layer and the second wurtzite type piezoelectric thin film, and improves the crystal orientation of the second wurtzite type piezoelectric thin film (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 4117376 Summary of the Invention [Problem to be solved by the invention]

[0008] In high-frequency devices such as BAW filters, there is a demand for even higher frequencies in anticipation of 5G communications using sub-6 GHz and millimeter wave bands. When using a piezoelectric thin film as the operating principle, the driving frequency is determined by the film thickness of the piezoelectric thin film. To achieve sub-6 GHz or higher frequencies, high crystal orientation is required in the ultra-thin film region with a film thickness of several hundred nm.

[0009] In the above prior art document, a first wurtzite type piezoelectric thin film is inserted under the functional material layer to improve the lattice matching between the functional material layer serving as an electrode and the second wurtzite type piezoelectric thin film. However, the functional material layer and the wurtzite type piezoelectric layer have very different basic structures, so sufficient lattice matching is not achieved. It cannot be said that the method in the prior art document realizes a growth mechanism close to epitaxial growth with good crystal orientation.

[0010] In general, it is said that in thin film growth, even if the crystal orientation is disturbed in the early stages of growth, the thicker the film, the smaller the effect of the initial crystal disorder, and the better the crystal orientation. In the above prior art document, the second wurtzite type piezoelectric thin film is as thick as 1 μm, so the crystal orientation is considered to have improved to a certain extent.

[0011] However, when the second wurtzite type piezoelectric thin film is made thinner to accommodate high frequencies, the effect of initial crystal disorder increases, causing a problem in that sufficient crystal orientation suitable for high frequency devices cannot be obtained.

[0012] The present invention has been made in view of the above problems, and provides a piezoelectric device having sufficient crystal orientation even when the piezoelectric layer has a thickness in the submicron range. [Means for solving the problem]

[0013] In an embodiment, an orientation control layer is inserted to adjust the degree of alignment of the crystal growth between the stacked material layers, thereby promoting crystal growth and realizing a piezoelectric device with a wurtzite-type piezoelectric thin film having a crystal orientation close to that of an epitaxially grown layer.

[0014] In a first aspect of the present disclosure, a piezoelectric device includes: a first wurtzite thin film, a first hexagonal metal layer, a first electrode layer, a second hexagonal metal layer, and a second wurtzite thin film are laminated in this order; The first electrode layer is formed of a metal material having a higher acoustic impedance than the second wurtzite thin film. Effect of the Invention

[0015] With the above-described configuration, a piezoelectric device having good crystal orientation can be realized even when the piezoelectric layer has a thickness in the submicron range. [Brief description of the drawings]

[0016] [Figure 1A] FIG. 2 is a diagram showing a first configuration example of a laminate according to an embodiment. [Figure 1B] 1B is a schematic diagram of a piezoelectric device using the laminate of FIG. 1A. [Figure 2A] FIG. 4 is a diagram showing a second configuration example of a laminate according to an embodiment. [Figure 2B] 2B is a schematic diagram of a piezoelectric device using the laminate of FIG. 2A. [Diagram 3] FIG. 11 is a diagram showing the relationship between the degree of crystal orientation and the electromechanical coupling coefficient. [Figure 4] FIG. 2 is a diagram showing the crystal orientation in each configuration. [Diagram 5] 11 is a diagram showing the film thickness ratio R1 between a hexagonal metal layer and a first electrode, and the degree of crystal orientation. FIG. [Figure 6] FIG. 13 is a graph showing the film thickness ratio R2 between the first wurtzite thin film and the amorphous layer, and the degree of crystal orientation. [Figure 7] FIG. 13 is a diagram showing the film thickness ratio R3 between the first wurtzite thin film and the second wurtzite thin film, and the degree of crystal orientation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] In the embodiment, in order to realize a high-frequency piezoelectric device, the piezoelectric layer, which is the functional layer, is formed of a wurtzite-type thin film with a thickness of less than 1000 nm (submicron), preferably several hundred nm. In order to efficiently confine vibration energy in this thin piezoelectric layer, a metal with a higher acoustic impedance than the piezoelectric layer is used as the electrode. Due to the difference in acoustic impedance, elastic waves are reflected at the interface between the electrode and the piezoelectric layer, and the vibration energy is confined in the piezoelectric layer.

[0018] Acoustic impedance is expressed as the product of density and sound speed. Sound speed correlates with the elastic modulus of a material, and the higher the elastic modulus of a material, the faster the sound speed. For an electrode to have high acoustic impedance, it means that at least one of the density and Young's modulus of the electrode material is high. For dense (heavy) metals, when the Young's modulus is high, the conversion efficiency between electrical energy and acoustic energy is high.

[0019] On the other hand, as described below, the crystal orientation of the piezoelectric layer affects the efficiency of conversion between electrical energy and acoustic energy. The better the crystal orientation of the piezoelectric layer, the higher the energy conversion efficiency.

[0020] In order to grow the wurtzite thin film that will become the piezoelectric layer on the electrode with good crystal orientation, another wurtzite thin film is inserted as a base for the electrode. Furthermore, a hexagonal metal layer, which has the same crystal structure as wurtzite, is placed between the base wurtzite thin film and the electrode, and between the electrode and the wurtzite thin film that will become the piezoelectric functional layer.

[0021] In a preferred embodiment, an amorphous orientation control layer may be used in addition to the underlying wurtzite thin film and hexagonal metal layer to improve the crystal orientation.

[0022] This structure adjusts the alignment of crystal growth between adjacent layers in the stacking direction, realizing crystal growth close to epitaxial growth. The piezoelectric layer formed on the electrode has good crystal orientation even at a thickness of submicron, for example several hundred nm.

[0023] <Examples of the laminate and the piezoelectric device> 1A is a schematic diagram of a laminate 110 according to an embodiment. The laminate 110 includes an amorphous layer 12, a first wurtzite thin film 13, a first hexagonal metal layer 14, a first electrode layer 15, a second hexagonal metal layer 16, and a second wurtzite thin film 17, in this order, on a substrate 11. In this specification, terms indicating a hierarchical relationship in terms of position, such as "upper side," "lower side," "upper layer," and "lower layer," do not indicate an absolute positional relationship, but rather indicate a hierarchical position in the stacking direction of the device in order to facilitate understanding of the invention.

[0024] The type of substrate 11 is not limited, and any suitable material can be used, such as a silicon (Si) substrate, a glass substrate, a plastic substrate, etc. When a plastic substrate is used, it may be a flexible substrate that can provide flexibility to the device.

[0025] Examples of the plastic substrate that can be used include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), acrylic resin, cycloolefin polymer, polyimide (PI), etc. When the piezoelectric device 10 is used as a BAW filter, a part of the substrate 11 may be processed into a diaphragm shape.

[0026] The amorphous layer 12 may be omitted if the first wurtzite thin film 13 can be grown on the surface of the substrate 11 with good crystal orientation, but the insertion of the amorphous layer 12 improves the crystal orientation of the entire laminate. When an inorganic material is used for the amorphous layer 12, any material may be used as long as it improves the wettability between the substrate 11 and the first wurtzite thin film 13 and improves the crystal orientation of the first wurtzite thin film 13. As the inorganic amorphous layer 12, ITO (indium tin oxide), IZO (indium zinc oxide), IZTO (indium zinc tin oxide), IGZO (indium gallium zinc oxide), etc. may be used. Alternatively, Al2O3 and SiO x ZnO with added Al2O3, SiO x etc. may also be used.

[0027] When an organic material is used as the amorphous layer 12, any material may be used as long as it improves the crystal orientation of the first wurtzite thin film 13. The organic amorphous layer 12 may be made of an acrylic resin, a urethane resin, a melamine resin, an alkyd resin, a siloxane-based polymer, or the like.

[0028] The amorphous layer 12 may be a single layer, or may be a laminate of two or more layers. In the case of a laminate, it may be a laminate of an inorganic amorphous layer and an organic amorphous layer.

[0029] There is no particular limitation on the thickness of the amorphous layer 12, but it is preferably 3 nm or more and 100 nm or less, and more preferably 10 nm or more and 50 nm or less. If the thickness of the amorphous layer 12 is less than 3 nm, it is difficult to exert the function of orientation control. If the thickness of the amorphous layer 12 exceeds 100 nm, it becomes difficult to make the device thin.

[0030] The first wurtzite thin film 13 is disposed to improve the crystal orientation of the second wurtzite thin film 17. The first hexagonal metal layer 14, the first electrode layer 15, and the second hexagonal metal layer 16 formed on the first wurtzite thin film 13 reflect the crystal orientation of the first wurtzite thin film 13. The difference in basic structure between the first electrode layer 15 and the second wurtzite thin film 17 is alleviated, and the second wurtzite thin film 17 is grown with good crystal orientation on the electrode structure including the first electrode layer 15.

[0031] The first wurtzite thin film 13 preferably contains one or more compounds selected from zinc oxide (ZnO), aluminum nitride (AlN), gallium nitride (GaN), or indium nitride (InN) as a main component. The first wurtzite thin film 13 and the second wurtzite thin film 17 functioning as a piezoelectric layer may be made of the same material or different materials. From the viewpoints of crystal lattice matching and ease of manufacturing process, it is preferable that the first wurtzite thin film 13 and the second wurtzite thin film 17 contain the same compound as a main component.

[0032] The thickness of the first wurtzite thin film 13 is preferably 5 nm or more and 50 nm or less, and more preferably 10 nm or more and 30 nm or less. If the thickness exceeds 50 nm, it approaches the thickness of the second wurtzite thin film 17, which is the functional layer, and may cause unnecessary vibrations such as multiple resonances. If the thickness is less than 5 nm, it becomes difficult to sufficiently transmit the c-axis orientation of the first wurtzite thin film 13 to the upper layers.

[0033] The thickness of the second wurtzite thin film 17 is not particularly limited because the optimum value varies depending on the target resonance frequency. If the target resonance frequency is 6 to 10 GHz, the thickness is preferably 300 nm or less, and if it is 10 GHz or more, the thickness is preferably 200 nm or less.

[0034] The first hexagonal metal layer 14 and the second hexagonal metal layer 16 function as orientation control layers. Any material can be used as long as it is a hexagonal metal having the same lattice structure as wurtzite. Titanium (Ti), zirconium (Zr), hafnium (Hf), ruthenium (Ru), zinc (Zn), yttrium (Y), scandium (Sc), or a combination of these can be used.

[0035] The first hexagonal metal layer 14 and the second hexagonal metal layer 16 preferably contain the same compound as a main component because they function as orientation control layers that adjust the lattice matching.

[0036] The film thickness of the first hexagonal metal layer 14 and the second hexagonal metal layer 16 is preferably 5 nm or more and 50 nm or less, and more preferably 10 nm or more and 30 nm or less. If the film thickness is less than 5 nm, it becomes difficult to fully exert the function of adjusting the lattice matching. If the film thickness exceeds 50 nm, it approaches the thickness of the first electrode layer 15, and there is a risk that the first hexagonal metal layer 14 and the second hexagonal metal layer 16, which are the orientation control layers, function as if they were electrodes.

[0037] The first electrode layer 15 may be made of any material as long as it has a higher acoustic impedance than the second wurtzite thin film 17. As described above, in order to have a high acoustic impedance, a material with a high density and a high Young's modulus is desirable. Materials with high acoustic impedance and a high Young's modulus include molybdenum (Mo), tungsten (W), ruthenium (Ru), rhodium (Rh), titanium (Ti), and hafnium (Hf).

[0038] The thickness of the first electrode layer 15 is not particularly limited because the optimum value varies depending on the target resonant frequency. The first electrode layer 15 may be formed of the same material as the first hexagonal metal layer 14 and the second hexagonal metal layer 16 to form a single hexagonal electrode layer.

[0039] Like the first wurtzite thin film 13, the second wurtzite thin film 17 preferably contains one or more compounds selected from ZnO, AlN, GaN, and InN as a main component.

[0040] As described above, the thickness of the second wurtzite thin film 17 is not particularly limited because the optimum value varies depending on the target resonant frequency. For use in the sub-6 GHz band, the thickness of the second wurtzite thin film 17 is preferably 300 nm or less. Since the second wurtzite thin film 17 has a laminated base of the amorphous layer 12, the first wurtzite thin film 13, and the first hexagonal metal layer 14, the crystal orientation of the second wurtzite thin film 17 is good even if the thickness is 300 nm or less. The second wurtzite thin film 17 has good vibration characteristics in the thickness direction.

[0041] Fig. 1B is a schematic diagram of a piezoelectric device 10 using the laminate 110 of Fig. 1A. The piezoelectric device 10 has a second electrode layer 18 on the second wurtzite thin film 17 of the laminate 110. The second wurtzite thin film 17 generates an electric signal in response to the vibration of an electric field applied between the first electrode layer 15 and the second electrode layer 18.

[0042] The second electrode layer 18 may be made of any material as long as it is a conductive metal. From the viewpoint of improving the effect of trapping vibration energy, it is preferable that the material has a higher acoustic impedance than the second wurtzite thin film 17, and examples of materials that can be used include molybdenum (Mo), tungsten (W), ruthenium (Ru), rhodium (Rh), titanium (Ti), and hafnium (Hf).

[0043] 2A is a schematic diagram of a laminate 120 according to an embodiment. The laminate 120 has the same laminate structure as the laminate 110 in FIG. 1A, except that the laminate 120 does not have an amorphous layer 12. The laminate 120 has a first wurtzite thin film 23, a first hexagonal metal layer 24, a first electrode layer 25, a second hexagonal metal layer 46, and a second wurtzite thin film 27 in this order on a substrate 21. Even if an amorphous layer is not used, the first wurtzite thin film 23 and the first hexagonal metal layer 24 can reflect the lattice structure of the first wurtzite thin film 23 to the first electrode layer 25, thereby improving the crystal orientation of the second wurtzite thin film 27.

[0044] Fig. 2B is a schematic diagram of a piezoelectric device 20 using the laminate 120 of Fig. 2A. The piezoelectric device 20 has a second electrode layer 28 on the second wurtzite thin film 27 of the laminate 130. The second electrode layer 28 may be made of any material as long as it is a conductive metal, but from the viewpoint of improving the effect of trapping vibration energy, it is desirable for the second electrode layer 28 to have a higher acoustic impedance than the second wurtzite thin film 27. The second wurtzite thin film 27 generates an electric signal in response to the vibration of the electric field applied between the first electrode layer 25 and the second electrode layer 28.

[0045] <Evaluation of Piezoelectric Devices> Figure 3 shows the general relationship between the degree of crystal orientation and the electromechanical coupling coefficient, as shown in RS Naik, et al., IEEE TUFFC, 47, (2000)292.

[0046] The degree of crystal orientation on the horizontal axis is shown as the full width at half maximum (FWHM) of the peak waveform when the reflection from the sample surface is measured using the X-ray rocking curve method. The smaller the FWHM of the X-ray rocking curve, the better the crystal orientation of the piezoelectric material.

[0047] In the case of wurtzite crystals, the FWHM of the X-ray rocking curve obtained by measuring the reflection from the (0002) face of the crystal indicates the degree of parallelism of the crystals in the c-axis direction. The smaller the FWHM of the X-ray rocking curve, the better the c-axis orientation of the crystal.

[0048] k on the vertical axis 2 represents the electromechanical coupling coefficient. The electromechanical coupling coefficient indicates the efficiency of energy conversion between electrical energy and acoustic energy, determined for a piezoelectric body. The higher the energy conversion efficiency between electrical energy and acoustic energy, the more efficiently the piezoelectric device operates.

[0049] In order for the second wurtzite thin film 17 to function properly as a high-frequency piezoelectric device, the FWHM of the X-ray rocking curve is desirably 6° or less. In order for the piezoelectric device to function as a high-frequency device such as a BAW filter, the FWHM of the X-ray rocking curve is desirably 4° or less, at which point the electromechanical coupling coefficient begins to saturate.

[0050] In the following, we evaluate what kind of device configuration is desirable to have good piezoelectric characteristics. We fabricate several samples with different configurations and evaluate the FWHM by the X-ray rocking curve method.

[0051] Figure 4 shows the evaluation results of the samples. As configuration parameters, the presence or absence of the amorphous layer 12 is taken in the vertical direction, and the presence or absence of the first hexagonal metal layer 14 and the second hexagonal metal layer 16 is taken in the horizontal direction. All samples were produced under the same conditions except for the presence or absence of the amorphous layer 12 and the presence or absence of the first hexagonal metal layer 14 and the second hexagonal metal layer 16.

[0052] <Sample No.1> Sample No. 1 has the same laminated structure as the piezoelectric device 10 of the embodiment of FIG. 1. On a substrate of alkali-free glass, a 50 nm thick IZO film is formed as an amorphous layer by DC magnetron sputtering. A 30 nm thick ZnO film is formed as a first wurtzite-type thin film by RF magnetron sputtering. A 30 nm thick Ti film is formed as a first hexagonal metal layer, a 300 nm thick Mo film is formed as a first electrode layer, and a 30 nm thick Ti film is formed as a second hexagonal metal layer by DC magnetron sputtering. A 200 nm thick ZnO film is formed as a second wurtzite-type thin film by RF magnetron sputtering. The 200 nm thick ZnO film corresponds to a resonant frequency of about 15 GHz. All of the above film formations are performed without heating.

[0053] The reflection from the (0002) plane of the second ZnO thin film is observed by the X-ray rocking curve method, and the FWHM calculated from the peak is measured. The measured FWHM is 3.3°.

[0054] This FWHM falls within the range of 6° or less of the characteristics in FIG. 3, and further falls within the range of 4° or less that is suitable for a BAW filter.

[0055] <Sample No.2> Sample No. 2 has the same layered structure as the piezoelectric device 20 of the embodiment shown in FIG. 2, but does not use an amorphous layer.

[0056] On a non-alkali glass substrate, a 30 nm thick ZnO film is formed as a first wurtzite thin film by RF magnetron sputtering. A 30 nm thick Ti film is formed as a first hexagonal metal layer, a 300 nm thick Mo film is formed as a first electrode layer, and a 30 nm thick titanium film is formed as a second hexagonal metal layer by DC magnetron sputtering. A 200 nm thick ZnO film is formed as a second wurtzite thin film by RF magnetron sputtering. All of the above film formations are performed without heating.

[0057] The reflection from the (0002) plane of the second ZnO thin film is measured by the X-ray rocking curve method, and the FWHM calculated from the peak is measured. The measured FWHM is 6.0°. This FWHM falls within the range of 6° or less of the characteristics in Figure 3, and can function as a high-frequency piezoelectric device.

[0058] <Sample No.3> Sample No. 3 uses an amorphous layer, but does not use either a first or second hexagonal metal layer.

[0059] On a non-alkali glass substrate, a 50 nm thick IZO film is formed as an amorphous layer by DC magnetron sputtering. On the IZO, a 30 nm thick ZnO film (first ZnO) is formed as a first wurtzite thin film by RF magnetron sputtering.

[0060] A 300 nm thick Mo film is formed as the first electrode layer on the first ZnO by DC magnetron sputtering. A 200 nm thick ZnO film is formed as the second wurtzite thin film on the surface of the Mo electrode by RF magnetron sputtering. All of the above film formation is performed without heating.

[0061] The reflection from the (0002) plane of the second ZnO thin film is measured by the X-ray rocking curve method, and the FWHM calculated from the peak is measured. The measured FWHM is 8.8°. This FWHM is larger than the 6° characteristic in Figure 3, and is insufficient as the crystal orientation of a high-frequency piezoelectric device having a piezoelectric functional layer of several hundred nm.

[0062] <Sample No.4> Sample No. 4 uses an amorphous layer and a first hexagonal metal layer, but does not use a second hexagonal metal layer.

[0063] On a non-alkali glass substrate, a 50 nm thick IZO film is formed as an amorphous layer by DC magnetron sputtering. On the IZO, a 30 nm thick ZnO film (first ZnO) is formed as a first wurtzite thin film by RF magnetron sputtering. On the first ZnO, a 30 nm thick Ti film is formed as a first hexagonal metal layer, and a 300 nm thick Mo film is formed as a first electrode layer by DC magnetron sputtering. On the surface of the Mo electrode, a 200 nm thick ZnO film is formed as a second wurtzite thin film by RF magnetron sputtering. All of the above film formation is performed without heating.

[0064] The reflection from the (0002) plane of the second ZnO thin film is measured using the X-ray rocking curve method, and the FWHM calculated from the peak is measured. The measured FWHM is 17.5°. This FWHM is far from the range of 6° or less in the characteristics of Figure 3, making it difficult to operate as a piezoelectric device.

[0065] In sample No. 4, even though it uses an amorphous IZO layer, the FWHM deteriorates. This is thought to be because the insertion of Ti between the first ZnO and the Mo electrode distorted the Mo crystal lattice, and the second ZnO film was formed in a state where this distortion was not restored.

[0066] <Sample No.5> Sample No. 5 uses an amorphous layer and a second hexagonal metal layer, but does not use a first hexagonal metal layer.

[0067] On a non-alkali glass substrate, a 50 nm thick IZO film is formed as an amorphous layer by DC magnetron sputtering. On the IZO, a 30 nm thick ZnO film (first ZnO) is formed as a first wurtzite thin film by RF magnetron sputtering. On the first ZnO, a 300 nm thick Mo film is formed as a first electrode layer, and a 30 nm thick Ti film is formed as a second hexagonal metal layer by DC magnetron sputtering. On the Ti layer, a 200 nm thick ZnO film is formed as a second wurtzite thin film by RF magnetron sputtering. All of the above film formations are performed without heating.

[0068] The reflection from the (0002) plane of the second ZnO thin film is measured using the X-ray rocking curve method, and the FWHM calculated from the peak is measured. The measured FWHM is 15.3°. This FWHM is far from the range of 6° or less of the characteristics in Figure 3, making it difficult to operate as a piezoelectric device.

[0069] In sample No. 5, even though it uses an amorphous IZO layer, the FWHM deteriorates. This is thought to be because the crystal lattice of the first ZnO reflected in the Mo electrode was distorted by the insertion of Ti between the Mo electrode and the second ZnO, and the second ZnO was deposited in this distorted state.

[0070] <Sample No.6> Sample No. 6 is a reference example and has a structure disclosed in the prior art. That is, neither an amorphous layer nor hexagonal metallicity is used. Although the structure is the same as that disclosed in the prior art, the deposition conditions of each layer are the same as those of Samples No. 1 to No. 5.

[0071] On a non-alkali glass substrate, a 30 nm thick ZnO (first ZnO) is deposited by RF magnetron sputtering as a first wurtzite thin film. On the first ZnO, a 300 nm thick Mo film is deposited by DC magnetron sputtering as a first electrode layer. On the Mo electrode, a 200 nm thick ZnO film is deposited by RF magnetron sputtering as a second wurtzite thin film. All of the above depositions are performed without heating.

[0072] In the prior art documents, a 1 μm-thick AlN layer is formed as the second wurtzite crystal layer, but since sample No. 6 is intended for use in a high-frequency device, the thickness of the second ZnO is set to 200 nm, similar to the other samples.

[0073] The reflection from the (0002) plane of the second ZnO thin film is measured by the X-ray rocking curve method, and the FWHM calculated from the peak is measured. The measured FWHM is 24.2°. This FWHM is farther away from the range of 6° or less in Figure 3 than Sample No. 4 and Sample No. 5.

[0074] In the prior art, the disturbance in the crystal orientation at the initial stage of growth is restored by increasing the thickness of the second wurtzite crystal layer to 1 μm. However, it is found that the disturbance in the crystal orientation is not restored in a thin film having a thickness of 200 nm such as Sample No. 6.

[0075] From the results in Figure 4, it can be seen that the crystal orientation is improved by sandwiching the high acoustic impedance (heavy) electrode layer between hexagonal metal layers on both sides, and that the crystal orientation of the wurtzite thin film is further improved by using an amorphous layer as an orientation control layer.

[0076] <Film thickness consideration> 5 shows the film thickness ratio R1 and the degree of crystal orientation between the first hexagonal metal layer 14 (or 24) and the first electrode layer 15 (or 25). Ti is used as the first hexagonal metal, and Mo is used as the first electrode. For each of sample numbers 11 to 14, the Ti / Mo ratio (R1) is changed to measure the full width at half maximum (indicated as "FWHM" in the figure) of the X-ray rocking curve.

[0077] In sample number 11, the Ti film thickness is 30 nm and the Mo film thickness is 300 nm. The Ti / Mo ratio is 1 / 10. The full width at half maximum of the X-ray rocking curve at this time is 3.3°, which is favorable.

[0078] In sample numbers 12 and 13, the Ti film thickness is 30 nm, the same as in sample number 11, and the Mo film thickness is changed to 90 nm and 200 nm, respectively. The Ti / Mo ratio of sample number 12 is 1 / 3, and the full width at half maximum of the X-ray rocking curve is 2.8°, which is good. The Ti / Mo ratio of sample number 13 is 3 / 20, and the full width at half maximum of the X-ray rocking curve is 2.7°, which is good.

[0079] In sample number 14, the Ti film thickness is set to 25 nm, and the Mo film thickness is set to 100 nm. The Ti / Mo ratio of sample number 14 is 1 / 4, and the full width at half maximum of the X-ray rocking curve is a good 3.3°.

[0080] In sample numbers 11 to 14, the Ti / Mo ratio is in the range of 1 / 10 to 1 / 3. By setting the film thickness ratio R1 in this range, the crystal orientation of the upper layer second wurtzite thin film 17 and 27 is improved. By setting the Ti / Mo ratio to 1 / 10 to 1 / 3, the full width at half maximum of the X-ray rocking curve is 3.3° or less, and the device operates appropriately as a high-frequency device such as a BAW filter. In sample numbers 12 and 14, the total film thickness of the first hexagonal metal layer 14 (or 24) and the first electrode layer 15 (or 25) is reduced to about 120 nm, improving the crystal orientation of the upper functional layer and making the device thinner. In sample numbers 11 and 13, the Mo layer with high acoustic impedance is made several hundred nanometers thick to sufficiently confine vibration energy and improve the crystal orientation of the upper functional layer.

[0081] The evaluation result in Fig. 5 is also valid for the film thickness ratio between the second hexagonal metal layer 16 (or 26) and the first electrode layer 15 (or 25). This is because a stack including the first wurtzite thin film, the first hexagonal metal layer, the first electrode layer, the second hexagonal metal layer, and the second wurtzite thin film in this order is symmetrical in the stacking direction with the first electrode layer as the center, and when an X-ray rocking curve is measured on the surface of the first wurtzite thin film, a result similar to that in Fig. 5 is obtained.

[0082] 6 shows the film thickness ratio R2 and the degree of crystal orientation of the first wurtzite thin film 13 or 23 and the amorphous layer 12. ZnO is used as the first wurtzite thin film 13 or 23, and IZO is used as the amorphous layer. For each of sample numbers 21 to 24, the ZnO / IZO ratio (R2) is changed and the FWHM of the X-ray rocking curve is measured.

[0083] In sample number 21, the ZnO film thickness is 30 nm and the IZO film thickness is 50 nm. The ZnO / IZO ratio is 3 / 5. The full width at half maximum of the X-ray rocking curve in this case is 3.3°, which is favorable.

[0084] In sample number 22, the IZO film thickness is 50 nm and the ZnO film thickness is 50 nm. The ZnO / IZO ratio is 1 / 1. The full width at half maximum of the X-ray rocking curve is 4.0°, which is favorable.

[0085] In sample number 23, the ZnO film thickness is 30 nm and the IZO film thickness is 100 nm. The ZnO / IZO ratio is 3 / 10. The full width at half maximum of the X-ray rocking curve is 2.5°, which is favorable.

[0086] In sample number 24, the ZnO film thickness is 20 nm and the IZO film thickness is 100 nm. The ZnO / IZO ratio is 1 / 5. The full width at half maximum of the X-ray rocking curve is 2.5°, which is favorable.

[0087] In sample numbers 21 to 24, the ZnO / IZO ratio ranges from 1 / 5 to 1 / 1. By setting the film thickness ratio R2 within this range, the crystal orientation of the upper second wurtzite thin films 17 and 27 is improved. In this R2 range, the full width at half maximum of the X-ray rocking curve is 4.0° or less, and the BAW filter can function appropriately.

[0088] FIG. 7 shows the film thickness ratio R3 and the degree of crystal orientation of the first wurtzite thin film 13 or 23 and the second wurtzite thin film 17 or 27. ZnO is used as the first wurtzite thin film and the second wurtzite thin film. For each of sample numbers 31 to 34, the thickness of the first ZnO film / the thickness of the second ZnO film (indicated as "first / second ratio" in the figure) is changed to measure the FWHM of the X-ray rocking curve.

[0089] In sample number 31, the thickness of the first ZnO is 30 nm, and the thickness of the second ZnO is 200 nm. The thickness ratio of the first ZnO / second ZnO is 3 / 20. The full width at half maximum of the X-ray rocking curve in this case is 3.3°, which is favorable.

[0090] In sample number 32, the thickness of the first ZnO is 30 nm, and the thickness of the second ZnO is 900 nm. The thickness ratio of the first ZnO / second ZnO is 1 / 30. By increasing the thickness of the second ZnO to 900 nm, the crystal lattice is well-ordered, and the full width at half maximum of the X-ray rocking curve is improved to 2.5°.

[0091] In sample number 33, the thickness of the first ZnO is 50 nm, and the thickness of the second ZnO is 150 nm. The ratio of the first ZnO to the second ZnO is 1 / 3. The full width at half maximum of the X-ray rocking curve is 4.2°. This value is sufficiently good for a high-frequency piezoelectric device, suggesting the possibility of application to BAW filters, etc.

[0092] In sample number 34, the thickness of the first ZnO is 30 nm, and the thickness of the second ZnO is 120 nm. The ratio of the first ZnO to the second ZnO is 1 / 4. The full width at half maximum of the X-ray rocking curve is 2.7°, which is favorable.

[0093] The first ZnO / second ZnO ratio ranges from 1 / 30 to 1 / 3 in sample numbers 31 to 34. By setting the film thickness ratio R3 within this range, the crystal orientation of the upper second wurtzite thin films 17 and 27 becomes very good.

[0094] As described above, even when the thickness of the second wurtzite thin film 17 or 27 as the functional layer is reduced to about several hundreds of nm in accordance with the sub-6 GHz band or higher, good crystal orientation can be obtained. In actual use, the substrate 11 or 21 may be omitted.

[0095] The piezoelectric device according to the embodiment can be applied not only to high-frequency bandpass noise filters for smartphones, but also to driving actuators for precision positioning devices and optical scanners for in-vehicle LiDAR (Light Detection and Ranging). [Explanation of symbols]

[0096] 10, 20 Piezoelectric devices 11, 21 Board 12 Amorphous layer 13, 23 First wurtzite thin film 14, 24 First hexagonal metal layer 15, 25 1st electrode layer 16, 26 Second hexagonal metal layer 17,27 Second wurtzite thin film 18,28 Second electrode layer 110, 120 Laminate

Claims

1. a first wurtzite thin film, a first hexagonal metal layer, a first electrode layer, a second hexagonal metal layer, and a second wurtzite thin film are laminated in this order; the first electrode layer is formed of a metal material having a higher acoustic impedance than the second wurtzite thin film and a material different from that of the first hexagonal metal layer and the second hexagonal metal layer; the second wurtzite thin film has a thickness of less than 1 μm; an amorphous layer disposed under the first wurtzite thin film; Laminate.

2. the thickness of the first wurtzite thin film is 1 / 5 to 1 / 1 of the thickness of the amorphous layer; The laminate according to claim 1 .

3. A first wurtzite thin film, a first hexagonal metal layer, a first electrode layer, a second hexagonal metal layer, and a second wurtzite thin film are laminated in this order on a substrate; the first electrode layer is formed of a metal material having a higher acoustic impedance than the second wurtzite thin film and a material different from that of the first hexagonal metal layer and the second hexagonal metal layer; the second wurtzite thin film has a thickness of less than 1 μm; The substrate is a silicon substrate or an amorphous substrate. Laminate.

4. The thickness of the first hexagonal metal layer and the thickness of the second hexagonal metal layer are each 1 / 10 to 1 / 3 of the thickness of the first electrode layer. The laminate according to any one of claims 1 to 3.

5. the thickness of the first wurtzite thin film is 1 / 30 to 1 / 3 of the thickness of the second wurtzite thin film; The laminate according to any one of claims 1 to 4.

6. The second wurtzite thin film has a thickness of 300 nm or less. The laminate according to any one of claims 1 to 5.

7. The laminate according to any one of claims 1 to 6, a second electrode layer disposed on the second wurtzite thin film in a stacking direction; having the second electrode layer is formed of a metal material having a higher acoustic impedance than the second wurtzite thin film; Piezoelectric devices.

8. laminating a first wurtzite thin film, a first hexagonal metal layer, a first electrode layer, a second hexagonal metal layer, and a second wurtzite thin film in this order on a substrate; the first electrode layer is formed of a metal material having a higher acoustic impedance than the second wurtzite thin film and a material different from the first hexagonal metal layer and the second hexagonal metal layer; the second wurtzite thin film has a thickness of less than 1 μm; an amorphous layer is formed between the substrate and the first wurtzite thin film; A method for manufacturing a laminate.

9. laminating a first wurtzite thin film, a first hexagonal metal layer, a first electrode layer, a second hexagonal metal layer, and a second wurtzite thin film in this order on a substrate; the first electrode layer is formed of a metal material having a higher acoustic impedance than the second wurtzite thin film and a material different from the first hexagonal metal layer and the second hexagonal metal layer; the second wurtzite thin film has a thickness of less than 1 μm; The substrate is a silicon substrate or an amorphous substrate. A method for manufacturing a laminate.

10. laminating a first wurtzite thin film, a first hexagonal metal layer, a first electrode layer, a second hexagonal metal layer, a second wurtzite thin film, and a second electrode layer in this order on a substrate; the first electrode layer and the second electrode layer are formed of a metal material having a higher acoustic impedance than the second wurtzite thin film and a material different from that of the first hexagonal metal layer and the second hexagonal metal layer; the second wurtzite thin film has a thickness of less than 1 μm; an amorphous layer is formed between the substrate and the first wurtzite thin film; A method for manufacturing a piezoelectric device.

11. laminating a first wurtzite thin film, a first hexagonal metal layer, a first electrode layer, a second hexagonal metal layer, a second wurtzite thin film, and a second electrode layer in this order on a substrate; the first electrode layer and the second electrode layer are formed of a metal material having a higher acoustic impedance than the second wurtzite thin film and a material different from that of the first hexagonal metal layer and the second hexagonal metal layer; the second wurtzite thin film has a thickness of less than 1 μm; The substrate is a silicon substrate or an amorphous substrate. A method for manufacturing a piezoelectric device.

Citation Information

Patent Citations

  • Electronic device, substrate therefor, and method for manufacturing them

    JP2005056940A

  • Semiconductor device

    JP2009231981A

  • Laminate containing wurtzite crystal layer and method for producing the same

    JP4117376B2

  • Wurtzrite thin film, laminate containing wurtzrite crystal layer, and method for production thereof

    WO2004101842A1

  • Piezoelectric film, method of manufacturing same, piezoelectric film laminated body, and method of manufacturing same

    WO2019163494A1